Understanding the development of Information science in Croatia. co-word analysis of doctoral dissertations from 1978 to 2009 - Pečarić, Đilda (Array, 2012)
For the analysis of doctoral dissertations in information science in the Republic of Croatia (from 1978 to 2009), keywords are used in order to get an insight into the development of information science. By the method of co-word analysis of keywords with which doctoral dissertations are indexed, a network of clusters that match following scientific disciplines is obtained: archival and documentation science, librarianship, communicology, museology, information science, information systems and lexicography. By cluster and data visualization and the overview of keywords frequency, the development of subjects and the correlation of clusters in information science, during the period of thirty years in which doctoral dissertation are made, is shown. The results of the co-word analysis about the development of information science in the Republic of Croatia are shown according to time periods, but also according to affiliation to certain disciplines inside the information science.